Ventricular Tachycardia and Early Fibrillation in Patients With Brugada Syndrome and Ischemic Cardiomyopathy Show Predictable Frequency-Phase Properties on the Precordial ECG Consistent With the Respective Arrhythmogenic Substrate. (October 2015) - Calvo, David; Atienza, Felipe; Saiz, Javier; Martínez, Laura; Ávila, Pablo; Rubín, José; Herreros, Benito; Arenal, Ángel; García-Fernández, Javier; Ferrer, Ana; Sebastián, Rafael; Martínez-Camblor, Pablo; et al.
Abstract : Background—: Ventricular fibrillation (VF) has been proposed to be maintained by localized high-frequency sources. We tested whether spectral-phase analysis of the precordial ECG enabled identification of periodic activation patterns generated by such sources. Methods and Results—: Precordial ECGs were recorded from 15 ischemic cardiomyopathy and 15 Brugada syndrome (type 1 ECG) patients during induced VF and analyzed in the frequency-phase domain. Despite temporal variability, induced VF episodes lasting 19.6±7.9 s displayed distinctly high power at a common frequency (shared frequency, 5.7±1.1 Hz) in all leads about half of the time. In patients with Brugada syndrome, phase analysis of shared frequency showed a V1 –V6 sequence as would be expected from patients displaying a type 1 ECG pattern ( P <0.001). Hilbert-based phases confirmed that the most stable sequence over the whole VF duration was V1 –V6 . Analysis of shared frequency in ischemic cardiomyopathy patients with anteroseptal (n=4), apical (n=3), and inferolateral (n=4) myocardial infarction displayed a sequence starting at V1 –V2, V3 –V4, and V5 –V6, respectively, consistent with an activation origin at the scar location ( P =0.005). Sequences correlated with the Hilbert-based phase analysis ( P <0.001). Posterior infarction (n=4) displayed no specific sequence. On paired comparison, phase sequences during monomorphic ventricular tachycardia correlated moderately with VF ( P <0.001). Moreover, there was a dominant frequency gradient from precordial leads facing the scar region to the contralateral leads (5.8±0.8 versus 5.4±1.1 Hz; P =0.004). Conclusions—: Noninvasive analysis of ventricular tachycardia and early VF in patients with Brugada syndrome and ischemic cardiomyopathy shows a predictable sequence in the frequency-phase domain, consistent with anatomic location of the arrhythmogenic substrate. Abstract : Supplemental Digital Content is available in the text.